2002
DOI: 10.1063/1.1514571
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of dendrimers in dilute solution

Abstract: Conformations of isolated homo-dendrimers of G = 1 − 7 generations with D = 1 − 6 spacers have been studied in the good and poor solvents, as well as across the coil-to-globule transition, by means of a version of the Gaussian self-consistent (GSC) method and Monte Carlo (MC) simulation in continuous space based on the same coarse-grained model. The latter includes harmonic springs between connected monomers and the pair-wise Lennard-Jones potential with a hard core repulsion. The scaling law for the dendrimer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
93
0
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(119 citation statements)
references
References 32 publications
(36 reference statements)
20
93
0
6
Order By: Relevance
“…The generation dependent changes in the form factor have been measured with SAXS on PAMAM dendrimers by Prosa et al 2 All experimental results, in respect to the appearance of higher order maxima for high-generation (gу5) dendrimers [13][14][15][16][17] and the scattering contribution of the internal density fluctuations at high scattering vectors 13,14,16 -19 are in very good qualitative agreement with results obtained from various computer simulations.…”
Section: A Form Factormentioning
confidence: 59%
See 1 more Smart Citation
“…The generation dependent changes in the form factor have been measured with SAXS on PAMAM dendrimers by Prosa et al 2 All experimental results, in respect to the appearance of higher order maxima for high-generation (gу5) dendrimers [13][14][15][16][17] and the scattering contribution of the internal density fluctuations at high scattering vectors 13,14,16 -19 are in very good qualitative agreement with results obtained from various computer simulations.…”
Section: A Form Factormentioning
confidence: 59%
“…Scattering experiments [2][3][4][5][6][7][8][9][10][11][12] and computer simulation [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] can give valuable information about the shape and internal structure of dendrimers in terms of radial density distributions and the overall dimension of dendrimers. Both methods approach the problem from different directions.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of their use include lithographic materials, nanoscale catalysts, drug delivery systems, rheology modifiers, bioadhesives, and magnetic resonance imaging (MRI) contrast agents [3]. Though experimental studies [4][5][6][7][8][9], theory and simulations [10][11][12][13][14] have already brought about some insight into the way charged dendrimers react to various conditions, the research on them is far from being completed. For instance, the number of simulation papers is still very limited and some predictions reported in them contrast with experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between dendrimer size and encapsulation behavior was unclear. Both experimental data and computational modeling [190][191][192] have suggested that, rather than packing with a dense shell, dendrimers pack more with a dense core type of conformation. This generalization is particularly true for dendrimers dissolved in solvents of "poor" to "moderate" solvating power, which is often the case.…”
Section: Discussionmentioning
confidence: 99%